2016
DOI: 10.1080/0886022x.2016.1207050
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between red cell distribution width and early renal injury in patients with gestational diabetes mellitus

Abstract: Previous studies found that red cell distribution width was related to adverse cardiovascular events. However, few studies reported the relationship between red cell distribution width and early-stage renal injury in pregnant women with gestational diabetes mellitus. Using a cross-sectional design, 334 pregnant women with gestational diabetes mellitus were enrolled according to the criterion of inclusion and exclusion. Demographic and clinical examination data were collected. Depended on the urine albumin, stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…[28] Similarly, Cheng et al found RDW to be an independent predictor of early stage renal injury in GDM patients. [29] In the present study we showed significantly increased RDW in GDM patients and in regression analysis RDW came out to be an independent predictor of GDM. Our study included 359 pregnant women and had a larger sample size than the aforementioned studies.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…[28] Similarly, Cheng et al found RDW to be an independent predictor of early stage renal injury in GDM patients. [29] In the present study we showed significantly increased RDW in GDM patients and in regression analysis RDW came out to be an independent predictor of GDM. Our study included 359 pregnant women and had a larger sample size than the aforementioned studies.…”
Section: Discussionsupporting
confidence: 63%
“…Erdogan et al retrospectively investigated 68 patients with GDM and 61 health controls. [15,28,29] They found no difference between RDW levels; however, Yildiz et al reported significantly increased RDW values in GDM patients. [28] Similarly, Cheng et al found RDW to be an independent predictor of early stage renal injury in GDM patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of albuminuria, Afonso et al [ 18 ] analyzed 8,499 representative participants in the National Health and Nutrition Examination Survey and found that elevated RDW was independently associated with microalbuminuria. A few other studies have demonstrated the same relationship in smaller, high-risk groups of patients such as those with hypertension or diabetes [ 15 , 16 , 23 ]. However, the studies described above were cross-sectional in design, and only two other small longitudinal studies have been performed.…”
Section: Discussionmentioning
confidence: 63%
“…Cheng et al investigated a different potential diagnostic use of RDW in GDM ( 29 ). Using a cross-sectional design, they studied 334 pregnant women with GDM in order to evaluate the role of RDW in predicting early renal injury.…”
Section: Discussionmentioning
confidence: 99%